Mucor hiemalis mediated 14 alpha-hydroxylation on steroids: In vivo and in vitro investigations of 14 alpha-hydroxylase activity - Kolet, Swati P.; Haldar, Saikat; Niloferjahan, Siddiqui; Thulasiram, Hirekodathakallu V. (Steroids, 2014)
Transformation of testosterone and progesterone into synthetically challenging 14 alpha-hydroxy derivatives was achieved by using fungal strain Mucor hiemalis. Prolonged incubation led to the formation of corresponding 6 beta/7 alpha,14 alpha-dihydroxy metabolites. The position and stereochemistry of newly introduced hydroxyl group was determined by detailed spectroscopic analyses. The time course experiment indicated that fungal strain initiated transformation by hydroxylation at 14 alpha-position followed by at 6 beta- or 7 alpha-positions. Studies using cell-free extracts suggest that the 14 alpha-hydroxylase activity is NADPH dependent and belongs to the cytochrome P450 family. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: 14 alpha-Hydroxylase; Biotransformation; Mucor hiemalis; Progesterone; Testosterone